Genotyping of polymorphic effectors of Toxoplasma gondii isolates from China - Weisheng Cheng; Cong Wang; Ting Xu; Fang Liu; Faustina Pappoe; Qingli Luo; Yuanhong Xu; Fangli Lu; Jilong Shen (Parasites & Vectors, 2017)
Abstract Background Toxoplasma gondii is an opportunistic protozoan apicomplexan and obligate intracellular parasite that infects a wide range of animals and humans. Rhoptry proteins 5 (ROP5), ROP16, ROP18 and dense granules 15 (GRA15) are the important effectors secreted by T. gondii which link to the strain virulence for mice and modulate the host’s response to the parasite. Little has been known about these molecules as well as GRA3 in type Chinese 1 strains that show polymorphism among strains of archetypical genotypes. This study examined the genetic diversity of these effectors and its correlated virulence in mice among T. gondii isolates from China. Results Twenty-one isolates from stray cats were detected, of which 15 belong to Chinese 1, and 6 to ToxoDB #205. Wh6 isolate, a Chinese 1 strain, has an avirulent phenotype. PCR-RFLP results of ROP5 and ROP18 presented few variations among the strains. Genotyping of GRA15 and ROP16 revealed that all the strains belong to type II allele except Xz7 which carries type I allele. ROP16 amino acid alignment at 503 locus demonstrated that 17 isolates are featured as type I or type III (ROP16I/III), and the other 4 as type II (ROP16II). The strains investigated may be divided into four groups based on GRA3 amino acid alignment, and all isolates of type Chinese 1 belong to the μ-1 allele except Wh6 which is identical to type II strain. Conclusions PCR-RFLP and sequence alignment analyses of ROP5, ROP16, ROP18, GRA3, and GRA15 in T. gondii revealed that strains with the same genotype may have variations in some of their key genes. GRA3 variation exhibited by Wh6 strain may be associated with the difference in phenotype and pathogenesis.